Quantum Approach to Organizational Paradox: A Copenhagen Perspective - Li, Xin (Academy of Management Review, 2021)
Original paper: Tobias Hahn and Eric Knight, The ontology of organizational paradox: A quantum approach. https://doi.org/10.5465/amr.2018.0408 This paper comments on Tobias Hahn’s and Eric Knight’s quantum approach to the ontology of organizational paradox. By addressing the problems of their application of quantum physics to organizational paradox research, we aim to move the mainstream thinking on organizational paradox beyond the dominant ‘both/and’ thinking toward a ‘neither/nor’ thinking that is the essence of the Copenhagen Interpretation of quantum theory. We posit, embracing the ‘neither/nor’ thinking, just like the shift from the ‘either/or’ thinking to the ‘both/and’ thinking, affords management scholars a much broader cognitive space in which resolving paradox may not be, as the mainstream organizational paradox scholars currently think, impossible. In our alternative quantum approach to organizational paradox, any paradox or paradoxical tension is caused by the asymmetry between one’s capacity and expectation (ACE), and the principle of paradox resolution is then the reduction of the asymmetry by either increasing one’s capacities or decreasing one’s expectations or doing both simultaneously.